KRIMINALISASI KORPORASI DALAM TINDAK PIDANA KORUPSI TERKAIT BUMN PERSERO - Iqbal, Moch (Jurnal Hukum dan Peradilan, 2013)
Differences in the interpretation of the meaning of money the State and the State financial losses in our legal system relating to the criminalization of corporations has presented obscurity to universal norms and the law itself, when the offense of corruption seemed forced into a business cooperation agreement with the subject of international law involving other countries, raises international view that there is no rule of law in Indonesia. Should the option of thinking about state finances and the State loss, the choice is not on the Living Law (public will accept false), but the awareness of the public law that should be changed by law, Law as a tool of social engineering, so that law enforcement officers must actively change the legal awareness. Keywords: Corruption, corporations, State-Owned Limited